The exotic snail Rumina decollata (Linnaeus, 1758) (Gastropoda, Achatinidae, Rumininae) in Argentina: new records, range extension, and areas of origin of Argentine populations - Rau, Angemara Ivanna (2022)
The decollate land snail Rumina decollata (Linnaeus, 1758), native to the Mediterranean region, has been introduced across several countries worldwide. We report here three new records for R. decollata in Argentina, two from Córdoba Province and the first one from Misiones Province, which also constitutes the northernmost record for the country, extending its northeastern distribution range. Species-specific identification was achieved based on anatomical, conchological, and molecular information. DNA data showed that different haplotypes are present in Argentina, which originated from distinct source areas along the native range.